Slovenske pesmi o veliki vojni iz dveh tematskih izborov - Žerjal-Pavlin, Vita (Jezik in slovstvo, 2016)
The two thematic collections examined offer an interesting overview of Slovenian Poetry inspired by World War I. Clouds are Red (Oblaki so rudeči) published in 1988, seventy years after the end of the war, is a collection of poems edited by Janez Povše. Landscape of War (V vojni pokrajini) was published in 2014 by Marjeta Žebovec on the occasion of the Great War Centenary. Poems from both collections highlight various war motifs and contemplations, ranging from combat, patriotism and even dynasties, to explicit earnestness, and thus oppose the censorship and pressure exerted over Slovenian intellectuals by the Austrian authorities. Verses are uttered by first-person speakers who had engaged in war in different ways. There are recurrent ideological confrontations, as well as insights into peoples' destinies affected by war. Due to the considerable age differences between the authors of the poems, we also notice a range of poetic styles: neo-romantic, expressionist and even futuristic, as well as more traditional poetic expressions typical of 19th century Slovenian Poetry
Keywords: Slovene literature; slovenska književnost; slovenska poezija; vojni motivi; Povše, Janez: Oblaki so rudeči; Žebovec, Marjeta: V vojni pokrajini; svetovna vojna 1914-1918; antologije; literarne študije